Super-Utilizers of Inpatient Care in an Obstetrical Population: A Cross-Sectional Study - Keselowsky, Kerri; Rosen, Todd; Hadaya, Ola; Khan, Shama; Ananth, Cande V. (American Journal of Perinatology, 2022)
Objective The aim of the study is to estimate hospital charges (HC) and length of stay (LOS) for pregnancy and 6 weeks postpartum and to characterize the outliers who utilize a disproportionate share of health care resources.Study Design We performed a cross-sectional study of 500 subjects at a tertiary center between 2012 and 2014. Subjects were included who had inpatient status and an ICD-9 code for pregnancy; those with an ICD-9 code for ectopic pregnancy were excluded. Data were collected 266 days prior to the estimated date of delivery (EDD) and up to 42 days post-delivery. Medical diagnoses, obstetrical details, demographics, HC, and LOS were collected. Super-utilizers (SUs) were selected as patients with total HC exceeding $75,000, those who incurred $75,000 or less were assigned to the typical utilizer (TU) group.Results HC was positively skewed, with median's (interquartile range) of $151,143 (97,707–198,732) and $28,186 (19,292–38,943) among SUs and TUs, respectively. Despite the low proportion of SU patients (7%, n = 36), they accounted for 30% of charges. Similarly, SUs had longer LOS (16 vs. 3 days, p <0.05). They had earlier deliveries (34.5 vs. 38.5 weeks, p <0.05), higher cesarean section rates (69 vs. 35%, p <0.05), and more hysterectomies (8.3 vs. 0%, p <0.05). The most common complications in SUs were preterm labor (33.3 vs. 5.4%, p <0.05) and preterm premature rupture of membranes (25 vs. 3.9%, p< 0.05). The most common pre-existing condition in SUs was chronic hypertension (11.1 vs. 3%, p< 0.05).Conclusion Although SUs comprise only 7% of the obstetrical population, they account for almost a third of the total HCs; in turn, SUs are at risk of adverse outcomes. Targeting this population can guide efforts to improve maternal health through prevention, research, and personalized care. SUs may have clustering at hospitals with higher levels of care and this topic warrants further investigation with state and national level data.Key Points
Keywords: super-utilizer; pregnancy; hospital charges; length of stay; health care spending